Conversion of furfural to tetrahydrofuran-derived secondary amines under mild conditions. Issue 6 (6th March 2020) - Jiang, Shi; Muller, Eric; Jerôme, François; Pera-Titus, Marc; De Oliveira Vigier, Karine
Abstract : Catalytic conversion of furfural to secondary tetrafurfurylamine under mild conditions of temperature and hydrogen pressure. Abstract : The production of amino-containing compounds from biomass is an important goal of research programs. Starting from carbohydrate-based furfural, a simple and highly efficient system was developed for producing a library of secondary and tertiary tetrahydrofurfurylamines under mild conditions (25 °C/1 bar H2 ) with excellent yields (>90%). Commercially available Pd/Al2 O3 proved to be a suitable catalyst and exhibited outstanding performance.